Characteristics of anaphylaxis‐inducing IgG immune complexes triggering murine passive systemic anaphylaxis. Issue 2 (18th December 2012) - Jiao, D.; Liu, Y.; Lu, X.; Pan, Q.; Zheng, J.; Liu, B.; Liu, Y.; Wang, Y.; Fu, N.
Abstract: Background: With the broad and increasing application of therapeutic monoclonal antibodies (mAbs) in clinical settings, IgG‐induced allergic reactions, including passive systemic anaphylaxis (PSA), have attracted significant attention. However, it is not clear which types of IgG mAb–antigen complexes or IgG aggregates formed by antigen binding can trigger PSA, as not all immune complexes (ICs) are capable of triggering PSA. Here, we characterise mAb–antigen complexes capable of inducing murine PSA to evaluate and predict which ICs are able to induce PSA. Methods: Thirty‐six combinatory reactions with eight antigens and 27 corresponding mAbs were used to trigger PSA, which was defined by rectal temperature. Sandwich ELISA, passive cutaneous anaphylaxis (PCA) induction and flow cytometry analysis of CD16/32 (FcγRIII/II) expression were used to characterise the ICs. The dynamic concentrations of antigen in the peripheral blood were measured by ELISA. Results: Only 14 of the 36 ICs could trigger PSA and thus be termed anaphylaxis‐inducing immune complexes (Ai‐ICs). The Ai‐ICs could be characterised by constructing sandwich ELISA, inducing PCA and down‐regulating CD16/32 (FcγRIII/II) expression on blood neutrophils in vitro and in vivo . Additionally, the occurrence and severity of PSA was found to be associated with the instantaneous concentration of antigen in the peripheral blood in the presence of antibody. Conclusions: Only Ai‐ICs, not all ICs, could trigger IgG‐mediated PSA, which could be characterised by the above simple methods. The occurrence and severity of PSA was associated with the instantaneous concentration of antigen in the peripheral blood in the presence of antibody.